1999
DOI: 10.1021/es981021k
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic and Biological Transformation of Tetraalkoxysilanes and Trichloroethene/cis-1,2-Dichloroethene Cometabolism Driven by Tetrabutoxysilane-Degrading Microorganisms

Abstract: Attenuation of silicon-based organic compounds (tetraalkoxysilanes) by abiotic hydrolysis and biological mineralization was investigated. At Lawrence Livermore National Laboratory site 300, tetraalkoxysilanes are present along with trichloroethene (TCE) as subsurface contaminants. Under abiotic conditions, the alkoxysilanes such as tetrabutoxysilane (TBOS) and tetrakis(2-ethylbutoxy)silane (TKEBS) hydrolyze to 1-butanol and 2-ethylbutanol, respectively, and silicic acid. The rates of hydrolysis of TBOS and TKE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 13 publications
2
45
0
Order By: Relevance
“…Depletion of nitrate and sulfate in D3 relative to T5 also was consistent with alkoxysilane-induced anaerobiosis. Furthermore, the presence of 2-ethylbutanol and 2-ethylbutyrate^both representing transformation products of TKEBS previously observed in controlled laboratory experiments [15,17]^and the accumulation of acetate in D3 suggested that the microorganisms native to this subsurface habitat had adapted to the presence of TCE and were performing fermentative reactions including anaerobic transformation of the tetraalkoxysilane compound.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Depletion of nitrate and sulfate in D3 relative to T5 also was consistent with alkoxysilane-induced anaerobiosis. Furthermore, the presence of 2-ethylbutanol and 2-ethylbutyrate^both representing transformation products of TKEBS previously observed in controlled laboratory experiments [15,17]^and the accumulation of acetate in D3 suggested that the microorganisms native to this subsurface habitat had adapted to the presence of TCE and were performing fermentative reactions including anaerobic transformation of the tetraalkoxysilane compound.…”
Section: Resultsmentioning
confidence: 68%
“…An additional bene¢t of these compounds^that could not be explored in this work^is their potential for triggering aerobic cometabolism of chloroethenes [17]. Tetraalkoxysilanes and their respective hydrolysis products have been shown to serve as the primary substrates of aerobic enrichment cultures capable of co-oxidizing TCE and cis-DCE [17].…”
Section: Signi¢cance Of Tetrakis(2-ethylbutoxy)silanementioning
confidence: 98%
“…4 Si], contain four oxygen bridges from the central silicon atom to the corresponding organic (alkoxy) groups. These compounds are widely used as heat-exchange fluids, sealants, and lubricants because of their excellent thermal properties [24,[421][422][423]. At Lawrence Livermore National Laboratory site 300, these compounds along with trichloroethylene (TCE) were used in heat-exchanger pipes at their materials testing facility [421][422][423].…”
Section: Trinitrotoluenementioning
confidence: 99%
“…Specific research work related to the transformation of these compounds under environmental conditions is limited, and biological degradation of these compounds has not been investigated [423]. However, numerous hydrolysis studies have been conducted on the lower homologues of the tetraalkoxysilanes such as tetramethoxysilane and tetraethoxysilane [229,423]. These compounds hydrolyze abiotically to give the corresponding alcohols and silicic acid [424].…”
Section: Trinitrotoluenementioning
confidence: 99%
See 1 more Smart Citation